The Effect of Using Student Excretion System Worksheets Based on Problem Based Learning on Students' Mastery of Concepts - Iin Murtini; Supiana Dian Nurtjahyani (Bioedukasi: Jurnal Pendidikan Biologi, 2024)
Student worksheets are open material that can assist the learning process in class. The student worksheet is equipped with the syntax of the problem-based learning model. The existence of the PBL model encourages students to think by solving the problems presented in this student worksheet so that it can help students understand the material being studied. This research aims to determine the effect of using problem-based learning-based excretory system student worksheets on students’ mastery of concepts. This research method is quasi-experimental. This research was conducted at SMPN 7 Tuban in December 2022. The population of this research was class VIII students, while the sample for this research was class VIII E using Biology student worksheets and VIII D not using Biology student worksheets with each class totaling 30 students. Data collection techniques using test questions. The data obtained was then analyzed using SPSS with the Unpaired t-test. The results showed that the significance value of p (= 0.000) < α (0.05), meaning that there is a significant difference between students who use PBL-based worksheets and students who do not use PBL-based worksheets.